Experimental Research on Quasi Two-stage Compression Heat Pump with Flash Tank Vapor-injection Using R134a - Chai Yupeng; Ma Guoyuan; Xu Shuxue; Ding Ruochen; Yu Lihua (Zhileng xuebao)
In order to improve the stability and coefficient of performance of the air source heat pump, a scroll compressor refrigeration / heat pump system with flash tank was proposed using R134a, and the experiment platform was built. The compressor’s discharge temperature, power input, cooling capacity, heating capacity, coefficient of performances of the refrigeration/heat pump system were studied. Results showed that, under the condition of condensing temperature 45 ℃ and evaporating temperature from ﹣20 ℃ to 0 ℃, the discharge temperature of the vapor injection system was 6.2 ℃ lower than that of the single stage compression system, power input increased only 1.4% to 2.8%, the cooling capacity and cooling COPc are 19.8% and 17.6% higher than that of the single stage system, the heating capacity and heating COPh are 15.3% and 13.2% higher, respectively.